Direct-acting antiviral treatment for hepatitis C among people who use or inject drugs: a systematic review and meta-analysis. (November 2018) - Hajarizadeh, Behzad; Cunningham, Evan B; Reid, Hannah; Law, Matthew; Dore, Gregory J; Grebely, Jason
Summary: Background: There are concerns around poorer response to direct-acting antiviral (DAA) therapy for hepatitis C virus infection among people who use drugs. This systematic review assessed DAA treatment outcomes among people with recent drug use and those receiving opioid substitution therapy. Methods: Bibliographic databases and conference presentations were searched for observational studies and clinical trials assessing DAA treatment completion, sustained virological response (SVR), and loss to follow-up among people with recent drug use (injecting or non-injecting) and those receiving opioid substitution therapy. Meta-analysis was used to pool estimates and meta-regression to explore heterogeneity. Findings: 38 eligible studies, with 3634 participants, were included. The definition of recent drug use varied across studies, with drug use in the past 6 months and at the initiation of or during DAA therapy most commonly used. Among individuals with recent injecting or non-injecting drug use (21 studies; 1408 participants), treatment completion was 97·5% (95% CI 96·6–98·3) and SVR was 87·7% (95% CI 84·2–91·3). Among individuals receiving opioid substitution therapy (36 studies; 2987 participants), treatment completion was 97·4% (95% CI 96·5–98·3) and SVR was 90·7% (95% CI 88·5–93·0). Among individuals with recent injecting drug use (eight studies; 670 participants), treatment completion was 96·9% (95% CI 95·6–98·2) and SVR was 87·4% (95% CI 82·0–92·8). In meta-regression analysis, clinical trials ( vs observational studies; adjusted odd ratio 2·18, 95% CI 1·27–3·75; p=0·006) and higher mean or median age (1·07, 1·02–1·12; p=0·008) were significantly associated with higher SVR. Clinical trials (0·45, 0·22–0·94; p=0·033) and older age (0·94, 0·88–0·99; p=0·034) were also significantly associated with a lower proportion of participants lost to follow-up. Interpretation: Response to DAA therapy was favourable among people with recent drug use (including those who inject) and those receiving opioid substitution therapy, supporting broadening access in these populations. Funding: The Kirby Institute, UNSW Sydney, and National Health and Medical Research Council of Australia.